MEKANISME PENETAPAN HARGA (PRICE) DAN KEBIJAKAN PENENTUAN KEUNTUNGAN (PROFIT) DITINJAU DARI PERSPEKTIF EKONOMI ISLAM - Anggi Pratiwi Sitorus (At-Tanmiyah Jurnal Ekonomi dan Bisnis Islam, 2022)
Price and Profit are two things that become an important focus in economic activity. There are mechanisms and policies in determining prices that can be viewed from conventional and Islamic perspectives. Companies in maintaining a going concern or survival must pay attention to pricing and profit because the purpose of the determination is for the blessing and satisfaction of the customer or customer. This paper discusses the problem of concepts, types, determination mechanisms, determination strategies, determination objectives, influencing factors, as well as Islamic views on prices and profits. The type of research in this paper is to use comparative descriptive analysis with a comparative causal approach, which is a study that focuses on causal comparisons of actual problems by compiling, analyzing and interpreting. The method used in writing this thesis is library research, namely the writing taken by the researcher as a theoretical basis in collecting data from the library.